Optimization of Vitamin D Fulfillment for Pregnant Women in the First 1000 Days of Life to Prevent Stunting in Mertan Village, Sukoharjo Regency - Ayudia, Syefira; Ani, Nur; Sartika, Iik (Universitas Veteran Bangun Nusantara, 2025)
Stunting in Sukoharjo Regency ranks 9th in Central Java Province. According to the health profile data of Sukoharjo Regency (2023), the percentage of malnourished toddlers in Bendosari District ranks 4th in Sukoharjo Regency. According to data from the Village Midwife of Mertan as of January 16, 2025, the number of stunted toddlers is 20 cases and 1 pregnant woman with KEK(Chronic Energy Deficiency). The prevalence of vitamin D deficiency in Indonesia reaches 50% of the total population from various groups, including pregnant women. The goal is to optimize child development and growth by preventing stunting early through meeting the vitamin D needs of pregnant women. Method: The target for this activity is pregnant women in April 2025 totaling 16 at the Village Health Post in Mertan. This activity uses interactive lecture methods and comprehensive stunting prevention packages for mothers. The instrument is a questionnaire. The evaluation of the activity is assessed from the pretest and posttest scores. The results of the service show a general increase in knowledge of 38%. The service activity reached a attendance target of 75% of total participants. Itis expected to be carried out sustainably for that activity.